Management of shipping companies - Theotokas, Ioannis (Routledge maritime masters, 2018)
The maritime sector is dynamic and volatile, creating the need for continuous monitoring of the latest developments and their effects on the organisation, management and strategies of shipping companies. It examines the organisation and management of companies which manage ocean-going ships, emphasising the special characteristics of the industry and the framework created by these. This unique and accessible book is an ideal text for students in maritime studies programs as well as readers interested in learning about maritime businesses organisation and management.